1999
DOI: 10.1046/j.1365-2699.1999.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal gradients in benthic community composition in Western Atlantic estuaries

Abstract: Summary AimThe community composition of benthic macroinvertebrates from 295 estuarine sites was examined in order to either confirm or challenge established boundaries of zoogeographical provinces. We also investigated the postulate that, while local distributions were determined by natural habitat characteristics such as salinity, sediment type and depth, distributions on a large geographical scale would be correlated with temperature. LocationThe Atlantic coast of the United States (on a latitudinal gradie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
122
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(133 citation statements)
references
References 31 publications
(91 reference statements)
9
122
1
1
Order By: Relevance
“…Focusing only on the northern species, clades N1 and N2 were distributed in formerly glaciated areas and diverged markedly when compared with clades N3 or N4 (both of which occurred in nonglaciated areas). This break coincides with the Acadian-Virginian transition zone, where glaciation and physical gradients have been invoked to explain a similar discontinuity in coastal species (Engle and Summers 1999;reviewed by Wares 2002 ; Fig. 3).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Focusing only on the northern species, clades N1 and N2 were distributed in formerly glaciated areas and diverged markedly when compared with clades N3 or N4 (both of which occurred in nonglaciated areas). This break coincides with the Acadian-Virginian transition zone, where glaciation and physical gradients have been invoked to explain a similar discontinuity in coastal species (Engle and Summers 1999;reviewed by Wares 2002 ; Fig. 3).…”
Section: Discussionsupporting
confidence: 52%
“…In contrast, the apparent lack of physical barriers, coupled with high dispersal potential, suggests that evolutionary mechanisms differ in diverse marine communities (Palumbi 1994;Myers 1997). However, as history, mode of development, and biogeographic zones appear to explain population structure in coastal areas, they may also play an important role in the determination of patterns of marine biodiversity (Engle and Summers 1999;Collin 2001;Wares 2002;Graham et al 2003). Indeed, glaciation has caused increased diversification and lineage extinction in northern coastal habitats (Hewitt 2000;Edmands 2001;Wares and Cunningham 2001;Marko 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Corkum (1989) reported that latitude and distance from the Pacific Ocean were important factors in Pacific Northwest invertebrate assemblages. Latitudinal gradients are more well established as a controlling factor for benthic invertebrate assemblages in coastal-marine waters, with Engle and Summers (1999) reporting that local distributions were determined by natural habitat variables, larger geographic distributions were influenced more by water temperature, which is related to latitude.…”
Section: Geographic Locationmentioning
confidence: 99%
“…In the northwest Atlantic, biogeographic studies have identified major boundaries at Cape Hatteras, Cape Cod, and the mouth of the Bay of Fundy (Engle and Summers 1999;Wilkinson et al 2009;Hale 2010;Pappalardo et al 2015). Genetic studies of marine invertebrates spanning these boundaries show concordant patterns of population subdivision where coastal currents diverge at Cape Hatteras, and eddy-like currents at Cape Cod and the Bay of Fundy reduce alongshore transport of larvae (see Kelly et al 2006;Altman et al 2013;Govindarajan et al 2015).…”
Section: Introductionmentioning
confidence: 99%